Effect of initial soil properties on six‐year growth of 15 tree species in tropical restoration plantings. Issue 24 (15th November 2016) - Martínez‐Garza, Cristina; Campo, Julio; Ricker, Martin; Tobón, Wolke
Abstract: In restoration plantings in degraded pastures, initial soil nutrient status may lead to differential growth of tropical tree species with diverse life history attributes and capacity for N2 fixation. In 2006, we planted 1, 440 seedlings of 15 native tree species in 16 fenced plots (30 × 30 m) in a 60‐year‐old pasture in Los Tuxtlas, Veracruz, Mexico, in two planting combinations. In the first year, we evaluated bulk density, pH, the concentration of organic carbon (C), total nitrogen (N), ammonia ( NO 3 − ), nitrate ( NH 4 + ), and total phosphorus (P) in the upper soil profile (0–20 cm in depth) of all plots. The first two axes of two principal component analyses explained more than 60% of the variation in soil variables: The axes were related to increasing bulk density, NO 3 −, NH 4 +, total N concentration, and pH. Average relative growth rates in diameter at the stem base of the juvenile trees after 6 years were higher for pioneer (45.7%) and N2 ‐fixing species (47.6%) than for nonpioneer (34.7%) and nonfixing species (36.2%). Most N2 ‐fixing species and those with the slowest growth rates did not respond to soil attributes. Tree species benefited from higher pH levels and existing litter biomass. The pioneers Ficus yoponensis, Cecropia obtusifolia, and Heliocarpus appendiculatus, and the N2 ‐fixing nonpioneers Cojoba arborea, Inga sinacae, and Platymiscium dimorphandrum were promising for forest restoration on our site, given their high growth rates. Abstract : After six‐year of growth, life history category (pioneer and non‐pioneer tree species) and capacity to fix N2 of the 15 tree species established in restoration plantings was useful to predict their growth rates and response to initial soil properties; also, seed mass was useful to predict growth rates. Tree species benefited from higher pH levels and organic matter.